Modelling anhydrous weight loss of torrefied wood sawdust - Siti Raishan, Mohd Rashid; Nur Hazirah Huda, Mohd Harun; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (Elsevier Ltd, 2017)
Saw mill industries in Malaysia produce a large amount of biomass waste in the form of sawdust, especially from Cengal and Kulim wood species. One of the attractive options to utilize the available biomass is by converting it to an alternative biofuels via torrefaction process. During torrefaction process, biomass is thermally decomposed thus resulted in biomass weight loss which is known as an anhydrous weight loss (AWL). In this study, the kinetic parameters were predicted by two step reactions in series known as Di Blasi – Lanzetta model for both heating and isothermal phases to achieve the desired AWL of torrefied Cengal and Kulim sawdust at temperature of 240°C, 270°C, and 300°C. All kinetic parameters are estimated according to Arrhenius law and fitted to the experimental result. The mass yield results shows that at higher temperature of 300°C, the rate of degradation is higher compared to the lower torrefaction temperature for both Cengal and Kulim woods due to the hemicellulose and cellulose wood constituents. In conclusion, the Di Blasi – Lanzetta model is reliable to predict the AWL of Cengal and Kulim woods in achieving the desired torrefied biomass properties.